REALITAS SOSIAL DALAM VIDEO PERTUNJUKAN “UBRUG” BERJUDUL “HALIWU” - Zanuar Eko Rahayu (SENDIKRAF Jurnal Pendidikan Seni dan Industri Kreatif, 2023)
The purpose of the study is to find out and to describe social reality in the video of “ubrug”performance with the story of "Haliwu" performed by Ubrug Sentra Agata in the agenda ofLongser Festival in West Java and Banten in 2019. The content analysis based on Berger andLuckmann’s social construction theory was conducted putting forward 3 (three) forms ofreality, namely objective, symbolic, and subjective. Through the study, objective and symbolicrealities of performance are interpreted into subjective reality. Techniques of collecting datainclude video observation, interviews, and literature reviews. Data collected is subsequentlygrouped according to the discussion to be analysed. The result of the analysis demonstratesthat social reality in the story of “Haliwu” reveals the structure of high, middle, and lowerclass society. These three classes of society are involved in constructing social issues relatedto financier society, hoax, politeness principles in society, and the world of love amongteenagers. Symbolic reality presented is merely replicating objective reality and so it givesinsufficient space for subjective interpretation.